2014
DOI: 10.1371/journal.pone.0111741
|View full text |Cite
|
Sign up to set email alerts
|

Exercises in Hot and Humid Environment Caused Liver Injury in a Rat Model

Abstract: ObjectiveTo investigate injury pattern during intense exercises in hot and humid environment particularly on liver in a rat exertional heat stroke model.MethodsWe randomly divided 30 rats into a control group (CG), a normal temperature (25±2°C, 60%±5% humidity) exercise group (NTEG) and a high temperature and high humidity (35±2°C, 80%±10% humidity) exercising group (HTEG), each comprising 10 animals. The NTEG and HTEG rats were forced to run in a treadmill for 1 hour maximum at 20 rpm. We analyzed liver cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…It has been proposed that changes in AP may exert stress on atherosclerotic plaques, resulting in plaque rupture [ 26 ]. A heat stroke rat model found tissue damage during exercise in hot and humid environments, that was related to inflammation, oxidative stress and apoptosis [ 27 ]. High humidity may also cause dehydration, which can increase thrombotic risk [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that changes in AP may exert stress on atherosclerotic plaques, resulting in plaque rupture [ 26 ]. A heat stroke rat model found tissue damage during exercise in hot and humid environments, that was related to inflammation, oxidative stress and apoptosis [ 27 ]. High humidity may also cause dehydration, which can increase thrombotic risk [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently the detrimental effects of exercise have been reported in rat models [31,32]. Li et al [31] reported that rats which had exercise training only for 5 days showed oxidative stress-induced liver damage when the rats were forced to run in a treadmill for 1 hour at 13 m/min until exhaustion. Ramos et al [32] also reported that an exposure of rats to single bout of swimming exercise causes elevation of plasma liver enzymes and oxidative stress biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological functions of important tissues are affected by long-term, high-intensity exercise that may exceed the body's endurance 7 . Several clinical biochemical parameters considered biomarkers for evaluating physiological functions or status after exercise or training include aspartate aminotransferase (AST), alanine aminotransferase (ALT), lactate dehydrogenase (LDH), and creatine kinase (CK) 8 , 9 . The metabolic index, such as blood urea nitrogen (BUN), can be used to evaluate the metabolic status, and biomarkers, including blood urea nitrogen (BUN), LDH, CK, AST, and ALT, can also be applied to assess physiological fatigue and recovery 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%